Trump: The Art of the Deal - Trump, Donald J (Random House Publishing, 1987)
Donald J. Trump is the very definition of the American success story, continually setting the standards of excellence while expanding his interests in real estate, sports, and entertainment. He is a graduate of the Wharton School of Finance. An accomplished author, Mr. Trump has authored over fifteen bestsellers and his first book, The Art of the Deal, is considered a business classic and one of the most successful business books of all time. Mr. Trump has over eight million followers on social media and is a frequent guest across a variety of media platforms.